Colorimetric analysis of leaves of plants exposed to cadmium. - Rodríguez Acevedo, Andrés Felipe; Velandia Torres, Lina Tatiana; Ramírez Rincón, Jorge Andrés; Reyes Roa, yulieth Catherine (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2023)
Cadmium is a toxic heavy metal which is absorbed, internalized, and translocated in plants in its divalent form Cd2+. The accumulation of cadmium in plant tissues at different concentrations represent significant phenotypic changes in plants and are initially expressed by leaves. In this study, morphological changes were evaluated by means of an analysis of variance for the colorimetric parameters of chroma, hue and gloss in leaves of Basil (Ocimum Basilicum), Peppermint (Mentha spicata), Lettuce (Lactuca sativa) and Spinach (Spinacia oleracea) plants grown under the floating root method in solutions containing cadmium at 100 µg/L. The results obtained indicate significant changes in each of the parameters considering the exposure time. The methodology used in this work can contribute significantly to the food safety problem by identifying and monitoring the effects of cadmium on food safety.